TAFSIR AYAT-AYAT TAKDIR DALAM KONTEKS DEMOKRASI MODERN: (Studi Analisis Kontestasi Pilpres 2024) - Moh Soim; Muhammad Zahid (EL-ADABI : Jurnal Studi Islam, 2024)
This research examines the role of verses of destiny in the context of the Indonesian presidential election in 2024. The scope of the research includes analyzing the interpretation of verses of destiny and their relevance to contemporary political dynamics. The main objective of the research is to understand the relationship between people's belief in destiny and the presidential election process, and to explore the psychological and spiritual factors that influence voter behavior. The methodology used is a qualitative approach with a descriptive-analytical nature, which integrates two main perspectives: politics and theology. From a political perspective, this research examines how people's belief in the verses of destiny influenced the dynamics of the presidential election, including campaign strategies and the perception of victory as part of divine providence. Meanwhile, from a theological perspective, in-depth analysis is conducted on the interpretation of Quranic verses on destiny to understand how spiritual values guide people's attitudes in facing political contestation.  Data were collected through literature studies, analysis of Quranic texts, and observation of relevant current socio-political phenomena. The collected data were then described in detail and analyzed to reveal patterns and meanings relevant to the research objectives. The results show that people's perception of destiny has a significant influence on attitudes and behaviors in political contestation. The findings highlight the importance of understanding the spiritual aspect in the dynamics of presidential elections, where victory is seen as a manifestation of divine providence, while still emphasizing the role of human effort in the process. This research makes an important contribution to understanding the interaction between religious beliefs and the democratization process in Indonesia.